The Geometric Accuracy of Complex Surface Using 5-Axis Turn-mill Machine - Khairul Jauhari; Mahfudz Al Huda (Universitas Brawijaya, 2020)
This paper presents an analysis model for geometric accuracy measurement of marine propeller blades. Geometric accuracy of marine propeller models, which has been finished by machining processes are measured and analyzed using GOM 3D photo-scanning peripheral and software. The methods we used are firstly, marine propeller blades are scanned by GOM Scanner and then the effects of cutting parameters, that is step-over variation on the geometric accuracy are investigated. Inspection of geometric accuracy is performed by comparing the result of 3D scanning measurement of finished propeller with CAD design data using GOM Inspect 2016 software. The results showed that greater step-over value, the deviation value tends to be smaller. Finally, this method is proven effective in measuring by producing similar trends at two measurement position points.